CONTRIBUTION AT SATELLITE ALTITUDE OF ELECTROMAGNETICALLY INDUCED ANOMALIES ARISING FROM A THREE-DIMENSIONAL HETEROGENEOUSLY CONDUCTING EARTH, USING SQ AS AN INDUCING SOURCE FIELD - Grammatica N.; Tarits P. (My University, 2002)
The induced magnetic signature at satellite altitude associated with crustal and mantle electrical heterogeneities is examined using five different Earth models. The three-dimensional induction problem is solved in these models using the solar quiet daily variation as an inducing source field. Every model has an upper shell representing the land–ocean electrical conductivity distribution. The different models have either a homogeneous mantle or a heterogeneous mantle containing either subduction zones, a ridge system or conductive blocks. Electromagnetic anomalies, presented in the form of geographical maps, are calculated for wavelengths related to spherical harmonics of degrees in the ranges 1–12 and 13–27, respectively. Magnetic anomalies are calculated at an altitude of 400 km and for three different local times: 6, 12 and 18 h.